2019
DOI: 10.1016/j.intfin.2018.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Risk, culture and investor behavior in small (but notorious) Eurozone countries

Abstract: This research investigates how culture moderates the impact of risk on individual investors' trading behavior in nine Eurozone countries, where risk is measured by conventional and extreme risk. These markets were particularly affected by the global financial crisis, the subsequent European banking crisis, and the European sovereign debt crisis. Using mutual fund flows as proxy of investors' trading behavior, our evidence indicates that country culture variable significantly affects investor' trading responsiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…According to the scholars, risk culture encompasses the ways in which collectives perceive a disruptive event, show trust towards involved authorities and ascribe responsibility of (consequences of) the event (Reuter et al, 2019, p. 3). Focusing on four European countries (Italy, Germany, The Netherlands and the UK), they present and compare the results of a survey on more than 7,000 people, concluding that the notion of risk culture offers an interesting theoretical framework and proposing an alternative to individualistic models of risk perception (Lee et al, 2019). Validating that Germany has a state-oriented risk culture, The Netherlands an individualistic one and Italy a fatalistic risk culture (Cornia, 2015;Cornia et al, 2016), Reuter et al (2019) are the first to study the UK, which is classified in the countries with a fatalistic risk culture.…”
Section: A Possible Explanation Of the Limited Integration Of The Research Communitymentioning
confidence: 99%
“…According to the scholars, risk culture encompasses the ways in which collectives perceive a disruptive event, show trust towards involved authorities and ascribe responsibility of (consequences of) the event (Reuter et al, 2019, p. 3). Focusing on four European countries (Italy, Germany, The Netherlands and the UK), they present and compare the results of a survey on more than 7,000 people, concluding that the notion of risk culture offers an interesting theoretical framework and proposing an alternative to individualistic models of risk perception (Lee et al, 2019). Validating that Germany has a state-oriented risk culture, The Netherlands an individualistic one and Italy a fatalistic risk culture (Cornia, 2015;Cornia et al, 2016), Reuter et al (2019) are the first to study the UK, which is classified in the countries with a fatalistic risk culture.…”
Section: A Possible Explanation Of the Limited Integration Of The Research Communitymentioning
confidence: 99%
“…In general, investment is always influenced by market conditions, the country's economic conditions, macroeconomic conditions, the political situation, and the security of a country. However, in a more in-depth analysis, it turns out that a country's culture is also a factor that influences investors' habits in determining the investment they will choose (Afego, 2018;Arisanti & Oktavendi, 2020;Lee, Switzer, & Wang, 2019). Investors' habits in acting when investing will also affect the value of investments in the market.…”
Section: Introductionmentioning
confidence: 99%
“…Further, while studying the direct relationship between individual attributes and non-economic goals of investors, the collectivism has also been found as a significant attribute affecting the investors' decisions regarding non-economic goals. Evidence is reported for other European countries, too, where the impact of culture is found significant on an individual's decision making (Lee et al, 2018). But current research has produced results in contrast to this and collectivism is found as an insignificant attribute.…”
Section: Conclusion and Discussionmentioning
confidence: 69%
“…The individual investors' behaviour is affected by the culture to which they belong. In a research-based on nine European countries, i.e., Austria, Sweden, Denmark, Belgium, Greece, Finland, Portugal, Norway, and Ireland, the authors found that culture has a significant impact on investors' response to risk (Lee et al, 2018). In the Indian context, Collectivism has been ascribed to the Indian culture's prominence on family, sense of empathy and community (Kulkarni et al, 2010).…”
Section: Defining Different Attributes Of Individual Investor's Charamentioning
confidence: 99%